2017
DOI: 10.1111/ced.13056
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in moderate to severe vitiligo using a novel combination of 308 nm excimer laser and a surgical needling technique

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In one study, 308-nm laser and microneedling yielded significantly better repigmentation than laser therapy alone. 14 A meta-analysis of 2 studies comparing NB-UVB and microneedling versus NB-UVB alone revealed lower odds of treatment failure (<25% repigmentation) with microneedling (OR 0.21, 95% CI 0.11–0.52, p = .0003) (see Supplemental Digital Content , Figure S1, http://links.lww.com/DSS/B91). 15,16 Side effects of microneedling were generally minimal and primarily included transient pain, pruritus, minor bleeding, and discomfort during or shortly after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, 308-nm laser and microneedling yielded significantly better repigmentation than laser therapy alone. 14 A meta-analysis of 2 studies comparing NB-UVB and microneedling versus NB-UVB alone revealed lower odds of treatment failure (<25% repigmentation) with microneedling (OR 0.21, 95% CI 0.11–0.52, p = .0003) (see Supplemental Digital Content , Figure S1, http://links.lww.com/DSS/B91). 15,16 Side effects of microneedling were generally minimal and primarily included transient pain, pruritus, minor bleeding, and discomfort during or shortly after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Response to treatment was measured using the Global Assessment Score every four weeks for up to sixteen weeks. Results showed that Group 2 achieved a statistically higher score (P < 0.001) compared to Group 1 [4]. They concluded that the addition of needling technique fifteen minutes prior to exposure to the laser gave a significantly better result [4].…”
Section: Vitiligomentioning
confidence: 98%
“…Meanwhile, needling is the use of 27G needles to treat skin conditions such as vitiligo [4]. The size of the needle is larger than the microneedles in Dermaroller and Dermapen.…”
mentioning
confidence: 99%
“…Moreover, a possible mechanical migration of melanocytes from the pigmented borders to the depigmented areas has been postulated. [ 89‐91 ] The wounding action of chemical peels has been reported in patients with vitiligo. Treatment with 88% phenol peeling in stable vitiligo lesions produced a repigmentation of 82.5% of hairy sites and 81.3% of non‐hairy .…”
Section: Proposed Treatmentsmentioning
confidence: 99%